Aspek Keagamaan Dan Sosial Budaya Dalam Pengembangan Bank Syariah di Lombok - Muslihun Muslim (Ulumuna, 2005)
The current presence of shariah banking in Indonesia seems more glittering than any other islamic economic institutions, such as Reksadana Syari‘ah, BMT, Syirkah Ta’awuniyah, Ahad Net Syari‘ah, and Asuransi Takafful. Regardless its complex background, it is primely caused by the significance of bank function in general, and specially by its products that are considered more suitable to the principles of the Qur’an and the Sunnah. They are considered more Islamic and promising justice. Shariah banking can be socialized through religious activities such as general sermon, but Muslims responds to its existance are so far still poor. It is indicated by fact that the development of many shariah banking was not followed by increasing omzets and deposits of their costumers’. Such a gap as in other places also happened in Lombok, an island with Muslim more than 90% of its population and welknown as “the one-tausand-mosque island”. What is “mistery” lying beyond the phenomena? Do the aspects of Muslim religiosity and culture in the island take role creating the gap? This article revealed answer to the questions that the formalistic mode of Muslim religious thought in the island caused the gap. Such mode of thought placed formal rituals as an ultimate criteria to see someone’s religiosity, piety, and even faith. It should be transformed to substantilistic mode of thought.